1995
DOI: 10.1021/ma00130a014
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Dynamical Homogeneity of the Dielectric α-Relaxation in Miscible Polymer Blends of Poly(epichlorohydrin) and Poly(vinyl methyl ether)

Abstract: The dielectric -relaxation of the poly(epichlorohydrin)/poly(vinyl methyl ether) miscible system is investigated in the frequency range 10-2-106 Hz. This polymer blend has the particularity that the components have nearly coincident glass-transition temperatures. We found that the relaxation spectra of these blends can be well described by the Kohlrausch-Williams-Watts law, the shape parameter being nearly temperature independent. This means that the dynamical heterogeneity commonly reported for the -relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 5 publications
2
39
0
Order By: Relevance
“…It is conjectured that decoupling of cooperative motions occur when the component with higher mobility (I) enhances the mobility of the component with lower mobility (II), but II does not retard the mobility of I so much. In polymer blend systems, for example, PI/PVE,3, 15 poly(ethylene oxide)/poly(methyl methacrylate),28 and poly(vinyl methyl ether)/PS,10 similar behavior is seen, that is the relaxation time of higher T g component decreases much by blending, but that of lower T g component is weakly dependent on blend composition.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…It is conjectured that decoupling of cooperative motions occur when the component with higher mobility (I) enhances the mobility of the component with lower mobility (II), but II does not retard the mobility of I so much. In polymer blend systems, for example, PI/PVE,3, 15 poly(ethylene oxide)/poly(methyl methacrylate),28 and poly(vinyl methyl ether)/PS,10 similar behavior is seen, that is the relaxation time of higher T g component decreases much by blending, but that of lower T g component is weakly dependent on blend composition.…”
Section: Resultsmentioning
confidence: 84%
“…Local dynamics in binary mixtures of glass formers, especially in polymer blends, has been attracting attention, since dynamically heterogeneous behaviors were observed in several systems 1–15. For example, Alegria et al3, 15 found the bimodal dielectric segmental relaxation spectra in polyisoprene/poly(vinyl ethylene) (PI/PVE) blends. Bimodal spectra indicate the decoupling of cooperative motions between components even in a mixed state.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of the chemical linkage between different polymer chains on the dynamics of disordered diblock copolymers (BCPs) also needs to be clarified. Many studies of dynamics in miscible blends1–24 and disordered block copolymers12, 25–30 have been performed thus far. Blends commonly exhibit broader relaxation spectra than those of the components.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed experimentally [49][50][51] that TTS is applicable to miscible polymer blends without specific interaction only when the difference in glass transition temperature (DT g ) between the constituent components is about 20 C or less. It is the general consensus among researchers that concentration fluctuations [52][53][54][55] and/or dynamic heterogeneity [53,[55][56][57][58][59][60][61] cause the failure of TTS in the miscible polymer blends without specific interaction when DT g is larger than about 20 C. Interestingly, however, in the present study we have found that TTS is applicable to both PC/ HPNBCOOH and P2VP/HPNBCOOH blend systems investigated in this study (see Figs.…”
Section: Discussionmentioning
confidence: 99%